PROSPECTIVE STUDY: COMPARISON OF PRONE AND SUPINE POSITION IN PERCUTANEOUS NEPHROLITHOTOMY (PCNL) AT ADAM MALIK HOSPITAL MEDAN - Maharddhika, Manggala; Kadar, Dhirajaya Dharma; Prapiska, Fauriski Febrian (Indonesian Journal of Urology, 2020)
Objective: This prospective study aims to compare the outcomes of PCNL with prone position compared to the supine position. Material & Methods: A total of 57 patients treated with PCNL from January 2017-December 2017 were included in the study. Inclusion criteria include patients with kidney stones greater than 20 mm in size measured with KUB imaging (Kidney-Ureter-Bladder) or abdominal NCCT (Non Contrast Computed Tomography) who were willing to be treated with PCNL. The exclusion criteria were patients younger than 17 years of age, patients who refused to surgery, patients with history of PCNL on the same side, patients with blood clotting disorders, pregnancy, and kidney stone in patients with congenital kidney disorders. Patients were randomized to undergo PCNL with prone or supine position. A total of 29 patients were treated with PCNL in prone position and 28 patients were treated in supine position. Data on patient characteristics, puncture location, number of puncture, use of post PCNL nephrostomy, duration of surgery, presence or absence of residual stones measuring ≥5 mm in size, total complications, postoperative fever, sepsis, bleeding requiring transfusion, retroperitoneal hematoma, pleural effusion, intestinal injury, and the difference between hemoglobin count before and after surgery was compared between the two groups. Results: There were no significant differences observed in terms of number, sex, age, BMI, stone size, hydronephrosis, and comorbidities in patients of both groups. Stone free rate in PCNL with prone position and supine position is 82.8% and 92.9% respectively. Significant comparisons were observed on differences in the mean duration of surgery in which PCNL duration of surgery with the prone position was 150 minutes whereas the supine position took 130 minutes (p=0.003). There were no significant differences between successful puncture, total complications, postoperative fever, sepsis, and bleeding requiring transfusion. There were no patients who had pleural effusion, intestinal injury, or death in this study. Conclusion: PCNL in supine position has the same effectiveness and safety as PCNL in prone position. The Stone free rate is higher in PCNL performed in supine position. The duration of PCNL surgery in supine position is significantly shorter than the PCNL prone position.